The Short and Long Run Benefits of Financial Integration - Colacito, Riccardo; Croce, Mariano M (American Economic Review, 2010)
There is an extensive economics and finance literature that addresses the potential benefits of financial integration. If on the one hand there is consensus on the significant inherent gain that may be attained in terms of portfolio diversification, decreased cost of equity capital, and reduced financing constraints, on the other hand, economics modeling has typically stumbled in the prediction of negligible welfare gains. Although the models adopted so far in the literature are able to accurately characterize the joint behavior of a large set of economic variables, they are typically silent about how closely they can track stock markets dynamics. Equivalently, it is still not clear what are the welfare benefits of financial integration when one wants to explain simultaneously prices and quantities. In order to address this point, we propose a general equilibrium model that is able to simultaneously explain: (i) the volatility of exchange rate and stochastic discount factors; and both (ii) the volatility of net exports and (iii) the amount of cross-country correlation and persistence of consumption growth rates. In our economy agents have risk-sensitive preferences in the sense of Hansen and Sargent (1995). This implies that investors have a preference for the timing of the resolution of uncertainty. We conduct our analysis for the case in which consumption is a Cobb-Douglas aggregation of domestic and foreign goods, both of which are tradable. Furthermore we let the dynamics of the growth rate of the endowments of ∗ Both authors are affiliated with the University